2019
DOI: 10.1111/cfs.12688
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in psychological distress, behavioural and emotional problems, and substance use in young people in out‐of‐home care

Abstract: The aim of the study was to examine sex differences in self‐reported psychological distress, behavioural and emotional problems, and substance use in young people living in out‐of‐home care (OoHC). One hundred seventy‐six young people aged 12–17 years (females 53.4%) in OoHC in metropolitan Melbourne, Australia, were interviewed. Participants completed self‐report measures: Kessler Psychological Distress Scale, Strengths and Difficulties Questionnaire, and the World Health Organization Alcohol, Smoking, and Su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…The mini-mental state examination scale [ 9 ] was used to assess the mental state of the patient. The scale has a full score of 30 points.…”
Section: Methodsmentioning
confidence: 99%
“…The mini-mental state examination scale [ 9 ] was used to assess the mental state of the patient. The scale has a full score of 30 points.…”
Section: Methodsmentioning
confidence: 99%
“…Other studies have also found that girls tended to run away more than boys (Courtney & Zinn, 2009; Dworsky, Wulczyn, & Huang, 2018). Cotton et al (2019) found that girls had more psychological distress, placement instability and sedative abuse. Therefore, it is reasonable to think that the emotional distress could be the factor underlying the riskier behaviours.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, it has been observed that rejected and neglected students are mostly male, while average and preferred students are mainly female [7]. It has also been observed that girls are more likely to experience emotional wellbeing problems [38,39], although some studies have reported a similar trend in both boys and girls [40][41][42]. One controversial aspect concerns the prevalence of cyber-aggression according to gender.…”
Section: Cyber-aggression and School Integrationmentioning
confidence: 99%